Unlocking the potential: exploring career management's impact on citizenship behavior among civil servants - Lee, Chin-Chin; Lim, Xin-Jean; Ng, Siew-Imm; Ho, Jo-Ann; Abdul Aziz, Yuhanis (Springer, 2025)
The Malaysian public service confronts a pressing challenge in delivering impactful performance that serves the society and the nation. Addressing this challenge, this study aims to investigate the intricate relationship between organizational career management practices, career competencies, career success, and organizational citizenship behavior (OCB). Drawing upon the social cognitive and social exchange theories, a comprehensive research model is constructed. Data were gathered from 605 civil servants who play pivotal roles in shaping, executing, and overseeing public policies. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM), the findings demonstrate a significant and positive influence of career management practices on OCB, with career competencies and career success acting as sequential mediators. Theoretically, this study emphasizes the necessity of balancing organizational and individual factors to enhance OCB performance. Practically, the study offers actionable insights for policymakers to formulate tailored strategies aimed at fostering organizational citizenship behavior, a pivotal element in achieving heightened performance among civil servants in Malaysia.